Lean model of service to increase the attention span of an automotive workshop - Tuesta, Victor (2019)
The sale of vehicles in Peru has increased by more than 6% only between the years 2016-2017, with Peru being one of the seven countries with an increase in vehicle fleet between these years, and it is also the fourth country with the highest sales, only after Brazil, Argentina and Chile. However, the post-sale service by the companies that provide these services currently does not meet certain essential aspects to meet the demand, one of the most outstanding, the delivery time, largely due to bad practices and capacity problems. of the concessionaire, generating considerable losses. Thus, this study developed a methodology to optimize the production of preventive maintenance services in automotive dealers applying lean manufacturing tools in order to reduce waiting times, delivery of vehicles at the wrong time and defective services. The pilot proposal was validated in one of the largest concessionaires of preventive maintenance service. The methodology reduced the lead time in two hours. The queues were reduced before each process and the percentage of vehicles delivered untimely from 28% to only 8% was reduced. In addition, the culture of good practices was implemented.